Toxoplasmosis in Pregnant Women and HIV/AIDS Patients in Ethiopia: A Systematic Review and Meta-Analysis - Daniel Getacher Feleke; Angesom Gebreweld; Gashaw Zewde (Journal of Parasitology Research)
Background. Although Toxoplasma gondii infection in immune-competent individuals is usually asymptomatic or causes a mild flu-like illness, it may become severe and can occasionally be fatal in immune-compromised people, such as AIDS patients or pregnant women. Method. Electronic English databases (Pubmed, Google Scholar, Science Direct, and Scopus), parasitology congresses, and theses of Ethiopian medical universities, were systematically searched (published or unpublished data). Full-length articles and abstracts were collected using keywords such as Toxoplasma gondii, Toxoplasmosis, pregnant women, HIV/AIDS, and Ethiopia. Results. Analysis of seroprevalence estimates was pooled using a random effects meta-analysis. Seventeen studies were included in the present systematic review and meta-analysis. One of these studies reported seroprevalence of T. gondii in HIV/AIDS patients and pregnant women. In this review, a total of 4,030 individuals were included and analyzed. The pooled prevalence of T. gondii in this review was 81.00% (95% CI = 69.10–89.78). Sub-group analysis showed that 2,557 pregnant women were evaluated. In pregnant women, the pooled sero-prevalence was 71.2 (95% CI = [51.9%, 87.1%]. In HIV/AIDS patients, 1,473 individuals were evaluated and the pooled seroprevalence was 88.45 (95% CI = 80.87%–94.31%). Conclusion. This systematic review and meta-analysis identified a high seroprevalence of Toxoplasma infection of 81% among immunocompromised patients. Scaling up prevention and control methods mainly strengthening educational efforts are necessary to avoid reactivation and to stop the spread of T. gondii infection.